Low-cost mapping of coastal geomorphology by remote sensing in Anjos Cove, Arraial do Cabo, Brazil - Vargas, Ruan; Wasserman, Julio Cesar de Faria Alvin; Santos, Camila Américo dos; Silva, Agenor Cunha da; Dias, Fábio Ferreira (Revista Brasileira de Geomorfologia, 2023)
Bathymetry is a crucial information for understanding coastal geomorphological processes. This study aims to evaluate the applicability of Satellite-Derived Bathymetry (SDB) as a low-cost alternative for coastal geomorphological mapping in Anjos Cove. Sentinel-2B images were used for generation of SDBs of coastal environments by two empirical methodologies. Depths were measured in situ by echo sounding for calibration and validation of the models. The models of Anjos Beach calibrated with 100% and 50% of the control points were evaluated for cost and time reduction. All SDBs of Anjos Beach presented similar geomorphological features and statistics results, with correlations of r ≅ 0.94 both in calibration and validation. When considering half of the control points for model calibration, the total cost for the mapping is estimated to reduce by approximately 50%. A SDB of a submerged sandbar was also mapped with a correlation of r ≅ 0.98 with depth field data. SDB can be used for a quick and low-cost assessment of the geomorphology in Anjos Cove. New SDB models can be evaluated from higher spatial resolution satellites to reduce errors.